Enhancing Local Tropical Beef Cattle Production Supporting Food Security in Indonesia - Margawati, Endang Tri (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Enhancing Local Tropical Beef Cattle Production Supporting Food Security inIndonesia